Reviews of Books (International review of mission, 1962)
MISSION AND UNITY: MISSION ET UNITÉ: LES EXIGENCES DE LA COMMUNION. By M. J. Le Guillou, OP. THE OECUMENICAL ENTERPRISE: THE ECUMENICAL MOVEMENT. By Norman Goodall. THE OECUMENICAL ENTERPRISE: BRÈVE HISTOIRE DE L'ŒCUMÉNISME. By Paul Conord. CHURCH UNIONS: KIRCHEN-UNIONEN DES 20. JAHRHUNDERTS. By Jürgen Wilhelm Winterhager. THE LAY APOSTOLATE: DAS LAIENAPOSTOLAT IN DEN MISSIONEN: Professor Dr Johannes Beckmann SMB zum 60. Geburtstag dargeboten von Freunden und Schülern. Herausgegeben von J. Specker, SMB, und W. Bühlmann THE CHURCH IN INDIA: AN INTRODUCTION TO INDIAN CHURCH HISTORY. By C. B. Firth. THE CHURCH IN AFRICA: CHRITSIANS OF THE COPPERBELT: THE GROWTH OF THE CHURCH IN NORTHERN RHODESIA. By John V. Taylor and Dorothea Lehmann. THE CHURCH IN AFRICA: SOME AFRICAN INDEPENDENT CHURCHES. By F. B. Welbourn. MISSIONARY PENETRATION IN FRENCH POLYNESIA: THE HISTORY OF THE TAHITIAN MISSION, 1799–1830, written by John Davies, missionary to the South Sea Islands, with Supplementary Papers from the Correspondence of the Missionaries. Edited by Colin W. Newbury. THE CHRISTIAN CITIZEN: THE THEORY AND METHOD OF CHRISTIAN EDUCATION. By W. M. Ryburn. THE CHRISTIAN CITIZEN: CHRISTIAN PARTICIPATION IN NATION BUILDING. Edited by P. D. Devanandan and M. M. Thomas. STUDIES IN ISLAM: STUDIA MISSIONALIA XI: ISLAM. Illustrated Edited by the Missiological Faculty of the Pontifical Gregorian University SOME THEOLOGIES CONCERNING MISSION: THE THEOLOGY OF THE CHRISTIAN MISSION. Edited and with an Introduction by Gerald H. Anderson. THAI LIFE AND CUSTOMS: LIFE AND RITUAL IN OLD SIAM. By Phya Anuman Rajadhon. THE DINKA: DIVINITY AND EXPERIENCE: THE RELIGION OF THE DINKA. by Godfrey Lienhardt. AUTHORITY AND DISCIPLINE IN AN AFRICAN PEOPLE: LUGBARA RELIGION: RITUAL AND AUTHORITY AMONG AN EAST AFRICAN PEOPLE. By John Middleton. MALAGASY RELIGIOUS BELIEFS: ASPECTS DE L'AME MALGACHE. By Pierre Colin. IN SEARCH OF AFRICA: THE NEW AFRICA. By Smith Hempstone. THE SIGNIFICANCE OF SUNDAY: SUNDAY: CHRISTIAN AND SOCIAL SIGNIFICANCE. By William Hodgkins. A SURVEY OF MODES OF WORSHIP: WORSHIP IN THE WORLD'S RELIGIONS. By Geoffrey Parrinder.